High temperature infrared absorption cross sections of methane near 3.4 µm in Ar and CO2 mixtures. (February 2018) - Koroglu, Batikan; Neupane, Sneha; Pryor, Owen; Peale, Robert E.; Vasu, Subith S.
Highlights: The first high temperature measurements of the absorption cross section of methane in excess CO2 bath gas around 3403 nm. Measurements conducted in a shock tube during pyrolysis and oxidation of methane between 700 < T < 2000 K and 0.1 < P < 1.5 atm. Additional measurements taken using FTIR at 1 atm and room temperature to study the effect of various bath gases. Data is valuable for developing laser schemes for measuring methane concentration in CO2 diluted mixtures for spectroscopy applications. Abstract: The absorption cross-sections of CH4 at two wavelengths in the mid-IR region: λpeak = 3403.4 nm and λvalley = 3403.7 nm were measured. Data were taken using three different compositions of non-reactive gas mixtures comprising CH4 /Ar/CO2 between 700 < T < 2000 K and 0.1 < P < 1.5 atm in a shock tube utilizing a continuous-wave distributed-feedback quantum cascade laser. Also, broadband room temperature methane cross section measurements were performed using a Fourier transform infrared spectrometer and the cascade laser to gain a better insight into the changes of the line shapes in various bath gasses (Ar, CO2, and N2 ). An application of the high-temperature cross-section data was demonstrated to determine the concentration of methane during oxy-methane combustion in a mixture of CO2, O2, and Ar. Current measurements will be valuable addition to the spectroscopy database for methane- an important fuel used for power generation and heating around the world.